Tindak Pidana Pencucian Uang Terhadap Perjudian Online - Satrya, Alda; Nugroho, Bastianto; Supolo, Supolo (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2022)
Law Number 8 of 2010 regulates the Prevention and Eradication of the Crime of Money Laundering. This law contains any provisions that can be a predicate crime in money laundering, one of which is a crime of online gambling. The legal rules that contain criminal sanctions in Law no. 8 of 2010 contained in articles 3 to 5 with a reverse proof system article 2 paragraph (1) where the defendant is obliged to prove the truth of all his assets. This study uses a normative method, using a legal approach (Statute Approach), a conceptual approach (Conceptual Approach) and data analysis (data analysis). The data collection method in this research is library research on legal materials, both primary legal materials, secondary legal materials, as well as tertiary legal materials and/or non-legal materials. The search for legal materials is done by reading, viewing or listening. or via the internet.